The Impact of Stock Liquidity on Corporate Cash Holding: The Role of Ownership Concentration in Indonesia - William Alfa Handoko; Arief Wibisono Lubis (Eduvest - Journal of Universal Studies, 2026)
Research Aims: This study aims to examine the influence of stock liquidity and ownership concentration on corporate cash holdings, including how ownership concentration moderates the relationship between liquidity and cash holdings in the context of an emerging market. Design/methodology/approach: The study employs a panel data approach using fixed-effects regression to analyze firms listed on the Indonesia Stock Exchange from 2019 to 2023. The sample is selected through purposive sampling to firms included in the Kompas100 Index. The amount of data used is 281 observation data. Research Findings: The findings show that higher stock liquidity, particularly turnover ratio, is significantly associated with lower corporate cash holdings, supporting the liquidity discipline hypothesis. Ownership concentration, measured by dominant shareholders’ equity stakes, positively and significantly affects cash holdings, consistent with principal–principal agency problems. However, the interaction term between stock liquidity and ownership concentration is negative and statistically significant, indicating that ownership concentration moderates the relationship by strengthening the negative association between stock liquidity and corporate cash holdings. Theoretical Contribution/Originality: This study provides empirical evidence that, in the context of an emerging market like Indonesia, ownership concentration may play a role in reinforcing the disciplinary effect of stock liquidity on corporate cash holdings.